Addressing Supply Chain Challenges in the Nigerian Construction Industry: The Role of Government Policies and Regulations - Esan, Ayodeji Augustine; Olowa, Theophilus Oluwarotimi Olatunde; Amuda-Yusuf, Ganiyu; Adebiyi, Ranti Taibat (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
This study explores the challenges and strategic solutions affecting supply chains in Nigeria’s construction industry, with a focus on government policy, regulatory barriers, and stakeholder coordination. Qualitative insights from industry professionals reveal that poor infrastructure, fragmented communication, and inconsistent regulations hinder supply chain efficiency. Although policy initiatives promoting local sourcing and improved procurement offer potential, persistent issues—such as customs delays and inadequate road networks—create ongoing bottlenecks. Ineffective coordination among contractors, suppliers, and agencies leads to cost overruns and project delays. The study highlights the value of digital platforms for real-time communication, collaborative planning, and transparency. It recommends regulatory reform, infrastructure upgrades, and the adoption of agile management and digital technologies. Enhancing supply chain performance will require coordinated efforts from government, industry, and regulators. The findings offer practical insights for policymakers and practitioners and suggest avenues for future research on digital integration and regional supply dynamics.